2011
DOI: 10.2215/cjn.11571210
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative Stress and Galactose-Deficient IgA1 as Markers of Progression in IgA Nephropathy

Abstract: Summary Background and objectives We assessed the activation of the oxidative stress pathway in patients with IgA nephropathy (IgAN), while evaluating the classic marker of the disease (galactose-deficient serum IgA1). Design, setting, participants, & measurements Sera from 292 patients and 69 healthy controls from Italy and the United States were assayed for advanced oxidation protein products (AOPPs), free sulfhydryl groups … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
80
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
4
1

Relationship

3
6

Authors

Journals

citations
Cited by 107 publications
(88 citation statements)
references
References 40 publications
7
80
1
Order By: Relevance
“…In another study, an increased serum level of aberrantly glycosylated IgA1 correlated with worse proteinuria. 24 Furthermore, in that study, the combination of a high serum Gd-IgA1 level and a high circulating level of advanced oxidation protein products correlated with a faster decline in eGFR, suggesting that oxidative stress may modulate the nephrotoxicity of aberrantly glycosylated IgA1.…”
Section: Discussionmentioning
confidence: 73%
“…In another study, an increased serum level of aberrantly glycosylated IgA1 correlated with worse proteinuria. 24 Furthermore, in that study, the combination of a high serum Gd-IgA1 level and a high circulating level of advanced oxidation protein products correlated with a faster decline in eGFR, suggesting that oxidative stress may modulate the nephrotoxicity of aberrantly glycosylated IgA1.…”
Section: Discussionmentioning
confidence: 73%
“…Camilla et al found elevated levels of advanced oxidation protein products in the sera of patients with IgAN, which correlated both with time-averaged proteinuria and with the rate of decline in eGFR (38). The association was strengthened by combining measurement of advanced oxidation protein products (AOPPs) with Gd-IgA1.…”
Section: Oxidative Stressmentioning
confidence: 99%
“…Systemic oxidative stress is an important mediator of the inflammatory damage triggered by nephritogenic immune complexes in IgAN (38). Camilla et al found elevated levels of advanced oxidation protein products in the sera of patients with IgAN, which correlated both with time-averaged proteinuria and with the rate of decline in eGFR (38).…”
Section: Oxidative Stressmentioning
confidence: 99%
“…Lectin-based assays progressed through a careful screening of GalNAc-specific binding (39) to the development of a quantitative ELISA (6). This assay was used for analyses of IgA1 in several clinical cohorts to demonstrate that most patients with IgAN have elevated serum levels of Gd-IgA1, including children and adults of various ethnicities (6,13,14,(40)(41)(42).…”
Section: Iga1 O-glycosylation Pathway and Anti-glycan Antibodies In Iganmentioning
confidence: 99%